– Adjustment of the Long- Term Investment Role in Omani Islamic Banks - An Empirical Study on Al- Izz Islamic Bank - Al- Ismail, Jabir Shoaib (Journal of Economic, Administrative and Legal Sciences, 2019)
Aim of the Paper: The study aimed to analyze the investment role of al- Izz Islamic Bank and its ability to make long- term investments، as well as to demonstrate the diversity of its fund- raising policies and its interest in long- term investments as a part of total fund employment when formulating its policy and recruitment strategy.Study Design: The researcher relied on the analytical descriptive approach and the case study of the Bank of al- Ezz from the final financial statements، where he worked on analyzing and extracting the results from it.Sample and Data: The data were collected by analyzing the bank's final financial statements، as well as analyzing the long- term investment policies of the Al- Izz Islamic Bank.Results: The results indicate that there has been a significant weakening of long- term investments، which has affected the bank's failure to contribute to economic and social development، while short- term financing operations have captured the largest proportion of its money- recruiting policies.Conclusion: The study was concerned with enriching knowledge about the long- term investment role of al- Izz Islamic Bank and its ability to contribute to economic and social development، thus having shed light and expanding interest in long- term investments.
Keywords: Islamic banks; investment; financing; Sultanate of Oman